2007
DOI: 10.2152/jmi.54.243
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum concentrations of saturated fatty acids and unsaturated fatty acids and the homeostasis model insulin resistance index in Japanese patients with type 2 diabetes mellitus

Abstract: Some PUFA as well as SFA were positively correlated with HOMA-R. These results indicate that the intake of diet fatty acid must be well balanced in diabetic patients and it is not always true to refrain from taking SFA and increase the unsaturated fatty acids in their diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 15 publications
3
38
1
Order By: Relevance
“…Presently, 20:2n-6 and 20:3n-3 are widely considered dead-end products, in part because their conversion to LCPUFA has not been unequivocally established (43). However, recent studies have associated 20:2n-2 with FADS2 polymorphisms and/or fatty acid compositions in humans (32,44), including patients with cardiovascular disease (31) and type 2 diabetes mellitus (45). In addition, apolipoprotein D knockout mice, a model for psychiatric disorders, show increased CNS 20:2n-6 and 18:2n-6 compared with wild-type mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, 20:2n-6 and 20:3n-3 are widely considered dead-end products, in part because their conversion to LCPUFA has not been unequivocally established (43). However, recent studies have associated 20:2n-2 with FADS2 polymorphisms and/or fatty acid compositions in humans (32,44), including patients with cardiovascular disease (31) and type 2 diabetes mellitus (45). In addition, apolipoprotein D knockout mice, a model for psychiatric disorders, show increased CNS 20:2n-6 and 18:2n-6 compared with wild-type mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…14). Similarly, multiple studies have also linked the SFA myristate (C14:0), which is a major constituent of milk fat, to insulin resistance and the metabolic syndrome in humans (14)(15)(16)(17). Strikingly, in wild-type C57BL/6J mice, this milk fat-based diet (MFBD) promoted profound insulin resistance and hyperglycemia by 8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of circulating palmitoleic acid in regulating insulin sensitivity in humans is unclear because of confl icting data from different studies, which have found that the percentage of palmitoleate in plasma FFA or lipids correlated directly with insulin sensitivity ( 3 ) or was greater in insulinresistant (IR) than insulin-sensitive (IS) subjects (4)(5)(6)(7)(8). Moreover, these studies did not measure absolute palmitoleate concentration, which provides a better assessment of palmitoleate availability to peripheral tissues, or palmitoleate within very low-density lipoprotein (VLDL), which may be an important contributor to tissue fatty acid delivery.…”
mentioning
confidence: 99%